Art and Architecture of Soviet Avant-garde in Critical Legacy of Vinicio Paladini - Babicheva, Mariia A. (Actual Problems of Theory and History of Art, 2024)
The artistic scene of Soviet Avant-garde was a subject of particular interest in the interwar period. Despite the political opposition in Fascist Italy, the phenomenon of the USSR was studied comprehensively, leaving room for both criticism of the regime and the acknowledgement of its achievements. Among the numerous Italian authors who wrote on the art of the Soviet Avant-garde, the figure of the artist, architect, and critic Vinicio Paladini stands out particularly. Despite his wide artistic and theoretical activity, the role of Vinicio Paladini has, to date, been studied rather superficially. Born in Moscow, Paladini was sympathetic to the USSR because of his political beliefs. He was deeply interested in Soviet fine art and architecture, as well as in the art of photomontage and cinema. Paladini’s critique of Soviet Avant-garde art consists of numerous publications which chronological span can be limited to 1925–1934. These include a brochure about the Soviet Pavilion at the 14th Venice Biennale, ‘Art in Soviet Russia. The USSR Pavilion in Venice’, and an article on Soviet constructivist architecture entitled ‘The Modern Spirit and the New Architecture in the USSR’ published in 1929 in the leading architectural journal Rassegna di Architettura. This list is complemented by articles on Soviet documentary cinema and on the art of photomontage. The present article offers a general overview and analysis of the publications by Vinicio Paladini based on the professional press and archival materials from the Russian State Archive of Literature and Arts, fully transcribed and translated into Russian by the author of the article for the first time.
Keywords: Vinicio Paladini; art and architecture of Soviet Avant-garde; constructivism; Italy-USSR cultural exchange; photomontage